A comprehensive assessment of caffeine’s effects on components of countermovement jump performance - Grgic, Jozo (Biology of Sport, 2022)
The aim of this study was to conduct a comprehensive examination of caffeine’s effects on countermovement jump (CMJ) performance. In this randomized, double-blind, crossover study, twenty-two resistance-trained men (age: 28 ± 5 years; height: 183 ± 5 cm; weight: 79 ± 10 kg; habitual caffeine intake: 127 ± 102 mg/day) performed the CMJ test on two occasions, following the ingestion of capsule containing 3 mg/kg of caffeine or placebo (3 mg/kg of dextrose). Fifteen outcomes derived from the force plate during the CMJ test were analyzed. As compared to placebo, there was a significant ergogenic effect of caffeine for peak force, force at eccentric to concentric action transition, time to peak force, peak power, maximum rate of power development, peak velocity, power at peak force, velocity at peak power, velocity at peak force, and vertical jump height. Effect sizes ranged from 0.11 to 0.38, p-values ranged from 0.048 to 0.002. There were no significant differences between caffeine and placebo for mean force, mean power, time to peak power, impulse at 300 ms, and force at peak power. This study shows that caffeine ingestion impacts a wide array of outcomes derived from the force plate during the CMJ test, not only jump height. From a practical perspective, the findings suggest that: (1) individuals interested in acute increases in CMJ performance may consider caffeine supplementation; and, (2) caffeine intake should be standardized before CMJ testing.